Targeting of the HER2/HER3 signaling axis overcomes ligand‐mediated resistance to trastuzumab in HER2‐positive breast cancer - Watanabe, Satomi (Cancer Med, 2019)
HER2‐targeted therapy, especially the anti‐HER2 antibody trastuzumab, is standard for HER2‐positive breast cancer; however, its efficacy is limited in a subpopulation of patients. HER3 ligand (heregulin)‐dependent HER2‐HER3 interactions play a critical role in the evasion of apoptosis and are therefore a target for oncotherapy to treat HER2‐positive breast cancer. The anti‐HER2 antibody pertuzumab and anti‐HER3 antibody patritumab both target this heregulin–HER3‐HER2 complex in different ways. This study examined the anticancer efficacy of dual HER2 and HER3 blockade in trastuzumab‐resistant HER2‐positive breast cancer. HER2‐positive SKBR3 or BT474 cells overexpressing heregulin (SKBR3‐HRG, BT474‐HRG) were used to evaluate the efficacy of trastuzumab, pertuzumab, and patritumab in vitro by performing cell viability, immunoblotting, and clonogenic assays. The effects of these agents were then evaluated in vivo using BT474‐HRG and an intrinsic heregulin‐expressing and HER2‐positive JIMT‐1 xenograft models. SKBR3‐HRG and BT474‐HRG cells lost sensitivity to trastuzumab, which was accompanied by Akt activation. Unexpectedly, trastuzumab in combination with pertuzumab or patritumab also showed limited efficacy toward these cells. In contrast, trastuzumab/pertuzumab/patritumab triple treatment demonstrated potent anticancer efficacy, concomitant with strong repression of Akt. Finally, in heregulin‐expressing BT474‐HRG and JIMT‐1 xenograft models, the addition of pertuzumab and patritumab to trastuzumab also enhanced antitumor efficacy leading to tumor regression. The current study found that triple blockade of HER2 and HER3 using trastuzumab, pertuzumab, and patritumab could overcome resistance to trastuzumab therapy in heregulin‐expressing and HER2‐positive breast cancer, which could be exploited clinically.